Ammonium‐Ion Storage Using Electrodeposited Manganese Oxides. Issue 11 (28th January 2021) - Song, Yu; Pan, Qing; Lv, Huizhen; Yang, Duo; Qin, Zengming; Zhang, Ming‐Yue; Sun, Xiaoqi; Liu, Xiao‐Xia
Abstract: NH4 + ions as charge carriers show potential for aqueous rechargeable batteries. Studied here for the first time is the NH4 + ‐storage chemistry using electrodeposited manganese oxide (MnO x ). MnO x experiences morphology and phase transformations during charge/discharge in dilute ammonium acetate (NH4 Ac) electrolyte. The NH4 Ac concentration plays an important role in NH4 + storage for MnO x . The transformed MnOx with a layered structure delivers a high specific capacity (176 mAh g −1 ) at a current density of 0.5 A g −1, and exhibits good cycling stability over 10 000 cycles in 0.5 M NH4 Ac, outperforming the state‐of‐the‐art NH4 + hosting materials. Experimental results suggest a solid‐solution behavior associated with NH4 + migration in layered MnO x . Spectroscopy studies and theoretical calculations show that the reversible NH4 + insertion/deinsertion is accompanied by hydrogen‐bond formation/breaking between NH4 + and the MnO x layers. These findings provide a new prototype (i.e., layered MnOx ) for NH4 + ‐based energy storage and contributes to the fundamental understanding of the NH4 + ‐storage mechanism for metal oxides. Abstract : NH4 + storage using electrodeposited manganese oxides (MnO x ) is studied for the first time. MnO x exhibits structural transformation during charge/discharge in dilute ammonium acetate (NH4 Ac) electrolyte. Experimental and theoretical results suggest that the reversible NH4 + insertion/deinsertion in layered MnO x is associated with hydrogen‐bond formation/breaking between NH4 + and the MnO x layers.